A Protocol for the Cryopreservation of Human Intestinal Mucosal Biopsies Compatible With Single-Cell Transcriptomics and Ex Vivo Studies - McRae, Alison; Ricardo-Silgado, Maria Laura; Liu, Yuanhang; Calderon, Gerardo; Gonzalez-Izundegui, Daniel; Rohakhtar, Fariborz Rakhshan; Simon, Vernadette; Li, Ying; Acosta, Andres (Frontiers in Physiology, 2022)
The heterogeneity of the human intestinal epithelium has hindered the understanding of the pathophysiology of distinct specialized cell types on a single-cell basis in disease states. Described here is a workflow for the cryopreservation of endoscopically obtained human intestinal mucosal biopsies, subsequent preparation of this tissue to yield highly viable fluorescence-activated cell sorting (FACS) isolated human intestinal epithelial cell (IEC) single-cell suspensions compatible with successful library preparation and deep single-cell RNA sequencing (scRNAseq). We validated this protocol in deep scRNAseq of 59,653 intestinal cells in 10 human participants. Furthermore, primary intestinal cultures were successfully generated from cryopreserved tissue, capable of surviving in short-term culture and suitable for physiological assays studying gut peptide secretion from rare hormone-producing enteroendocrine cells in humans. This study offers an accessible avenue for single-cell transcriptomics and ex vivo studies from cryopreserved intestinal mucosal biopsies. These techniques may be used in the future to dissect and define novel aberrations to the intestinal ecosystem that lead to the development and progression of disease states in humans, even in rare IEC populations.